THE MANAGEMENT OF THE LECTURERS’ EVALUATION SYSTEM IN THE COLLEGES AND UNIVERSITIES IN CHINA: PERIODS, CHANGES, OPPORTUNITIES AND CHALLENGES - Yunhong, Xu; Sulong, Rini Suryati; Huadong, Wang (Malaysian Journal of Business and Economics (MJBE), 2020)
Since the founding of the People’s Republic of China 70 years ago, the Lecturers’ Evaluation System in universities in China has undergone different periods of development, including initial formation, stagnation, recovery and adjustment, standardization and construction, development and deepening, and reform of classified evaluation. Each period presents different characteristics, and there are a series of changes in the subjects, methods, standards and application of evaluation results. Colleges and universities (mainly public institutions) have actively adapted and carried out a series of changes. Colleges and university lecturers should take the opportunities and challenges brought by the reform of Lecturers’ Evaluation System, positively change their roles as educators, researchers, social service providers and cultural disseminators; actively adjust their behaviours, actively assume the organizational citizenship behaviour; improve their academic titles, and promote the level of teaching and research. From the practice and experience of the Lecturers’ Evaluation System in 40 universities piloted by the Ministry of Education, the reform of the faculty members’ evaluation system has played a positive role in guiding, demonstrating and accumulating valuable experience in promoting colleges and universities in China.